A Self‐Independent Binary‐Sublattice Construction in Cu2Se Thermoelectric Materials - Zhao, Huijuan; Hu, Haihua; Jing‐Wei Li; Jing‐Feng Li; Zhu, Jing (Advanced functional materials, 2023)
The atomic‐scale structure of cuprous selenide room temperature phase (α‐Cu2Se), which plays an important role in understanding the mechanism of its high thermoelectric performance, is still not fully determined. Here, direct observation with atomic‐scale resolution is realized to reveal the fine structure of α‐Cu2Se via spherical‐aberration‐corrected scanning transmission electron microscopy. It is observed to be an interesting self‐independent binary‐sublattice construction for Cu and Se in α‐Cu2Se, respectively, which shows a variety of ordered copper fluctuation structures are embedded in a rigid pseudo‐cubic Se sublattice. Ordering of Cu uses a variety of configurations with little energy difference, forming considerable amounts of “boundaries,” which may lead to ultrastrong phonon scattering. Furthermore, density functional theory calculations indicate that the electronic structures are mainly determined by the rigid Se face‐centered cubic sublattice and not sensitive to the various copper fluctuations, which may guarantee the electron transfers with large carrier mobility. The self‐independent binary‐sublattice construction is speculated to enhance phonon scattering while still maintaining good electrical transport property. This study provides new critical information for further understanding the possible correlation between the specific structure and thermoelectric performance of α‐Cu2Se, as well as designing new thermoelectric materials.